2020
DOI: 10.4102/sajhivmed.v21i1.1085
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implementing same-day antiretroviral therapy initiation during routine care in Ekurhuleni District, South Africa: Retention and viral load suppression

Abstract: Background: Same-day initiation (SDI) of antiretroviral therapy (ART) has been advocated as an approach to increase linkage to care and overall ART initiation. Clinical trials have demonstrated impressive benefits. However, questions regarding patient preparedness and retention in care remain for routine implementation of this approach.Objectives: In this study, we sought to describe SDI of ART during routine care delivery and compare time to ART initiation on longitudinal care outcomes.Method: We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Overall 46 studies [2,20‐24,26‐30,32,40,43,45,49‐51,53,61,63,65,68,69,72,74‐94] reported on retention on ART or being on ART and 34 (74%) provided clear definitions of numerators and denominators. The majority of studies were longitudinal (29 studies, 63%), 13 were cross‐sectional and four of mixed design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations